GERMANIC NOMINATIONS OF BRITISH TITLES AND THEIR FUNCTIONING IN THE 19 th CENTURY FICTION TEXTS - Galina T. Bezkorovaynaya (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2020)
The article concerns identification of semantic potential of lexical units with a Germanic origin joined into thematic group “English titles of nobility”, and actualization of their meanings in the literary texts of the 19 th century. The sources of language material were the works of early Victorian period writers. The undertaken semantic and functional analysis of lexemes earl, knight, lord / lady enabled the author to conclude that when they indicate social status of the character depicted in the work of art or are used as an etiquette form of address, they implement direct meaning. It has been noted that alongside with lord / lady, the French loanwords sir / madame are used as forms of polite address in dialogues between the characters. The lexemes-titles can function in figurative meaning, i.e. knight maybe used to indicate valour as one of the main qualities of a noble person of high social status, Lord is used to denote the Creator, lady – to speak about any woman, as well as a wife, a mistress. The analysis of the data obtained resulted in deduction that in literary texts of the 19 th century the meanings of lexemes-titles, comprising thematic group English Nobility Titles, can express the following: the noble origin in the name of a person, a polite form of address in communication, nomination of a social status as well as some commonly shared character traits inherent to an aristocratic class representative; nomination of people in accordance with a family status or gender.